2019
DOI: 10.3390/w11061267
|View full text |Cite
|
Sign up to set email alerts
|

Priority Pollutants in Water and Sediments of a River for Control Basing on Benthic Macroinvertebrate Community Structure

Abstract: Understanding the drivers of macroinvertebrate community structure is fundamental for adequately controlling pollutants and managing ecosystems under global change. In this study, the abundance and diversity of benthic macroinvertebrates, as well as their chemical parameters, were investigated quarterly from August 2014 to April 2015 in four reaches of the Huai River basin (HRB). The self-organizing map (SOM) algorithm and canonical correspondence analysis (CCA) were simultaneously applied to identify the main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 47 publications
1
10
0
Order By: Relevance
“…Other authors in Nigeria have reported a similar level of sensitivities in freshwater macroinvertebrates [38,43]. Furthermore, the biomonitoring significance of aquatic insects, such as Ephemeroptera, Plecoptera, Trichoptera, and Odonata, have been widely reported by several aquatic scientists globally [26,28,41,44]. Our present study portrays the importance of identifying and categorizing river sites and macroinvertebrate taxa into pollution categories.…”
Section: Discussionsupporting
confidence: 74%
“…Other authors in Nigeria have reported a similar level of sensitivities in freshwater macroinvertebrates [38,43]. Furthermore, the biomonitoring significance of aquatic insects, such as Ephemeroptera, Plecoptera, Trichoptera, and Odonata, have been widely reported by several aquatic scientists globally [26,28,41,44]. Our present study portrays the importance of identifying and categorizing river sites and macroinvertebrate taxa into pollution categories.…”
Section: Discussionsupporting
confidence: 74%
“…WHO (2003) and Zheng et al (2012) also reported that metals can be retained over time in the bottom sediment and afterwards resorbed in the surface water during the re-suspension episode. Furthermore, other studies have also made similar observations that heavy metals concentrations of bottom sediments are usually higher than their surface water counterparts (Eddy et al, 2004;Malik and Maurya, 2015;Liu et al,2019). Heavy metals in sediment may be ingested by benthos (or pelagic organisms when the metals are reabsorbed into the water column) or absorbed by plants and thus enter the food chain where they bioaccumulate (Oboh and Edema, 2007).…”
Section: Heavy Metals In Bottom Sediment Of Cross Rivermentioning
confidence: 83%
“…Understanding the drivers of macroinvertebrate community structure is fundamental for adequately controlling pollutants and managing aquatic ecosystems under global change. Liu et al [14] analysed the characteristics of the environment and macroinvertebrate community in a river basin over time. They have established an approach by which to reveal community-environment relationships and identified priority pollutants that need to be controlled from the perspective of water ecological health protection.…”
Section: Background Investigationmentioning
confidence: 99%